Convenience and payment methods are determinants of students' shopping decisions in boarding houses in the Padang Bulan area, Medan. - Ester Agnesya Nainggolan; Darwis Robinson Manalu (Escalate : Economics and Business Journal, 2026)
The development of TikTok as a digital marketing medium This study aims to analyze the effect of price, service, comfort, product availability, and payment method on the shopping decisions of boarding-house students in the Padang Bulan area, Medan, at minimarkets and traditional markets. A quantitative approach was used with a purposive sampling technique involving 120 boarding-house students who had shopped at both minimarkets and traditional markets in the area. Data were collected through a five-point Likert-scale questionnaire and analyzed using multiple linear regression, preceded by validity, reliability, and classical assumption testing. The results show that all five independent variables simultaneously have a significant effect on shopping decisions, with a coefficient of determination of 0.669. Partially, comfort and payment method have a positive and significant effect on shopping decisions, while price, service, and product availability show no significant effect. Payment method is the most dominant variable influencing shopping decisions, followed by comfort. These findings indicate that transaction convenience and a comfortable shopping environment are the main considerations for boarding-house students when choosing where to shop, more than price, service quality, or product completeness. The findings suggest that both minimarket and traditional market managers should continue improving shopping comfort and expanding digital payment options to strengthen their competitiveness among student consumers.